2011
DOI: 10.4097/kjae.2011.61.5.405
|View full text |Cite
|
Sign up to set email alerts
|

Ramosetron for the prevention of postoperative nausea and vomiting (PONV): a meta-analysis

Abstract: BackgroundPostoperative nausea and vomiting (PONV) remains a challenge for patients and health professionals despite various newly developed prophylactic interventions. We reviewed the efficacy and safety of ramosetron in randomized controlled trials (RCTs) for the prevention of PONV.MethodsWe reviewed 18 randomized controlled trials investigating the efficacy and safety of ramosetron in comparison with placebo or any other drugs. Relevant studies were searched in the MEDLINE, SCOPUS, and the Cochrane database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…In the study by Lee [27], the effective dose of ramosetron for prophylaxis of PONV in high-risk patients was 0.6 mg, which was higher than the dose in our studies (0.3 mg). However, in the meta-analysis, 0.6 mg of ramosetron showed no greater benefits than 0.3 mg [25]. Also, significantly fewer instances of PONV occurred in the group that received 0.3 mg of ramosetron than in the placebo group [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Lee [27], the effective dose of ramosetron for prophylaxis of PONV in high-risk patients was 0.6 mg, which was higher than the dose in our studies (0.3 mg). However, in the meta-analysis, 0.6 mg of ramosetron showed no greater benefits than 0.3 mg [25]. Also, significantly fewer instances of PONV occurred in the group that received 0.3 mg of ramosetron than in the placebo group [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the meta-analysis, 0.6 mg of ramosetron showed no greater benefits than 0.3 mg [25]. Also, significantly fewer instances of PONV occurred in the group that received 0.3 mg of ramosetron than in the placebo group [25]. …”
Section: Discussionmentioning
confidence: 99%
“…[10] Many of the recent studies have shown that ramosetron is more effective than ondansetron in preventing PONV for the patients undergoing various other surgeries. [8111213] Furthermore, antiemetic efficacy of combination of ramosetron and dexamethasone was found to be similar to that of ondansetron and dexamethasone, when used as prophylaxis for the spine surgeries. [14] Addition of dexamethasone did not provide any advantage to ramosetron.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, ramosetron is more effective for reducing PONV than granisetron [15] or ondansetron [16,17]. In a meta-analysis, ramosetron 0.3 mg was consistently beneficial for preventing PONV (relative risk 0.4, 95% confidence interval (CI) 0.3-0.6), when compared to placebo, and it was also safe, producing no serious adverse events [18]. However, despite prophylaxis with ramosetron, PONV has still been reported in more than 30% of patients [15,17].…”
Section: Discussionmentioning
confidence: 99%